PEMILU 2009 DAN PERUBAHAN KONSTELASI PARTAI POLITIK: PERSPEKTIF PENDIDIKAN KEWARGANEGARAAN - Al-Rasyid, Machmud (PKn Progresif, 2008)
Change the constellation of political parties in the election of 2009 is not something real, because the high level of white groups as well as an electoral system that makes inflating the number of seats actually. The existence of citizens who are not registered and are not facilitated through an existing election mechanism violations of citizen rights. Phenomenon in the formation of coalition government between the parties and the winner of the defeated party will hurt the citizens because of the lack of alternative options on the next election, because all parties in the government coalition eventually. This means that the Election of 2009 does not reflect participation, but rather mobilization.